2015
DOI: 10.1074/jbc.m115.656660
|View full text |Cite
|
Sign up to set email alerts
|

The VCP/p97 and YOD1 Proteins Have Different Substrate-dependent Activities in Endoplasmic Reticulum-associated Degradation (ERAD)

Abstract: Background:The AAA-ATPase VCP/p97 and the deubiquitinase YOD1 are required in the endoplasmic reticulum-associated degradation (ERAD) of misfolded proteins. Results: Three ERAD substrates (NHK-␣1〈⌻, NS1-kLC, and Tetherin) become cytosolically exposed independently of p97 and YOD1, whereas MHC-I␣-and CD4-induced retro-translocation requires them. Conclusion: VCP/p97 and YOD1 have distinct substrate-dependent activities in ERAD. Significance: We demonstrate two different levels of p97 and YOD1 requirements in ER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 72 publications
1
24
1
Order By: Relevance
“…Indeed, experiments with the proteasome inhibitor MG132 indicated stabilization of the proteins resulting from stalled ribosomes. The same conclusions were obtained using the deubiquitinylase-like protein OTU or the YOD1-C160S, a dominant negative mutant of the ERAD-associated deubiquitinylase YOD1 [35,37,47] and the dominant negative mutant of the p97 ATPase (p97QQ). We also showed that cytosolic proteins produced from 2A* stalled free ribosomes were degraded by the proteasome.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…Indeed, experiments with the proteasome inhibitor MG132 indicated stabilization of the proteins resulting from stalled ribosomes. The same conclusions were obtained using the deubiquitinylase-like protein OTU or the YOD1-C160S, a dominant negative mutant of the ERAD-associated deubiquitinylase YOD1 [35,37,47] and the dominant negative mutant of the p97 ATPase (p97QQ). We also showed that cytosolic proteins produced from 2A* stalled free ribosomes were degraded by the proteasome.…”
Section: Discussionsupporting
confidence: 67%
“…5d). OTU removes ubiquitin from cytosolic poly-ubiquitinylated proteins targeted to degradation, impairing their engagement by the proteasome and therefore causing accumulation [35,36]. Similarly, co-expression with the dominant negative mammalian deubiquitinylase YOD1 (YOD1-C160S) [37] or the dominant negative mutant of the AAA p97 ATPase, which lacks ATPase activity (p97QQ, E305 and E578 mutated into Q) [38], blocked degradation of pr1 from construct 2A*, which accumulated intracellularly further confirming degradation through the ubiquitin-proteasome pathway (Fig.…”
Section: Proteasome Degradation Of Products Of Stalled Ribosomesmentioning
confidence: 99%
See 2 more Smart Citations
“…Valosin-containing protein, p97 (VCP/p97, Cdc48 in yeast) [10] is an abundant, conserved ATPase involved in diverse cellular activities, including ERAD, chromatin-associated degradation, mitochondria-associated degradation, and autophagy [11] , [12] , [13] . ERAD requires the retrograde (from ER to cytoplasm) transportation of unfolded proteins, which are ultimately destroyed by the ubiquitin-proteasome system.…”
Section: Introductionmentioning
confidence: 99%